TINDAK TUTUR ASERTIF DALAM DIALOG TALKSHOW MATA NAJWA DENGAN TEMA JAGA-JAGA TALIBAN DI MEDIA ELEKTRONIK - Firna Putri Nanda (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2022)
The purpose of this study is to describe assertive speech acts in the Mata Najwa talk show dialogue with the theme Jaga-Jaga Taliban in electronic media. The data obtained by the author comes from the utterances spoken by Najwa Shihab and sources in the talk show Mata Najwa on TRANS 7 which was re-aired on Najwa Shihab's Youtube channel, on August 26, 2021, with a duration of 1 hour 16 minutes 2 seconds. This research approach is using a qualitative approach. There are four forms of assertive speech acts, namely mentioning, showing, stating, and reporting. There were 9 speech acts stating, 21 showing speech acts, 64 stating speech acts, and 3 reporting speech acts. Based on the results of data analysis, it can be concluded that in understanding the meaning of language communication utterances contained in the Mata Najwa talk show dialogue with the theme Jaga-Jaga Taliban in electronic media, there are types of speech acts, one of which is assertive speech acts which include utterances of mentioning, showing, utterances declare, and utterances report. Therefore, in order to know and understand the speech intent of the assertive speech acts contained in the Mata Najwa talkshow dialogue with the theme Jaga-Jaga Taliban, one must carefully understand the intent of the speech act conveyed by the speaker.